2009
DOI: 10.1177/1548051809335360
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Senior-Level Executives on Effective Followership and Leadership

Abstract: Using a three-page questionnaire administered to a sample of 302 senior-level executives, this study examined the perceptions of executives on the distinguishing characteristics of effective leaders and followers. Most of the characteristics associated with effective leaders were perceived to be different from those associated with effective followers. A significant number of the respondents agreed that (a) leadership and followership are interrelated roles; (b) leadership and followership skills have to be le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 6 publications
2
70
0
Order By: Relevance
“…Agho (2009) noted that followership is viewed negatively and went further to state that followership was "seldom presented as an important trait for any person who aspires to lead others" (p.159). The best method to remove this stigma would be for the organisation's leaders to publicly recognise the value they attach to their followers; demonstrating that followership is an essential trait of leaders and the leadership within the organisation.…”
Section: Leadership and Followershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Agho (2009) noted that followership is viewed negatively and went further to state that followership was "seldom presented as an important trait for any person who aspires to lead others" (p.159). The best method to remove this stigma would be for the organisation's leaders to publicly recognise the value they attach to their followers; demonstrating that followership is an essential trait of leaders and the leadership within the organisation.…”
Section: Leadership and Followershipmentioning
confidence: 99%
“…Agho (2009) argued that "leaders must develop the skills to integrate effective followership into performance evaluation for all employees" (p. 165). One method to achieve this is to embed followership within the organisation's core ethos.…”
Section: Leadership and Followershipmentioning
confidence: 99%
“…For too long, leadership studies have been leader‐centered with little attention paid to the roles of followers in the leadership process. While the term leader has been glamorized, the term follower has been associated with passiveness, subservience, and lack of imagination (Agho, ). However, follower‐centric leadership scholars have argued that while leader‐follower roles are distinct, leaders and followers constantly switch between these roles (Baker, ; Crossman & Crossman, ).…”
Section: Introductionmentioning
confidence: 99%
“…It should be added here that in examining local union leadership behaviour, in addition to locating this in the history of the particular unions concerned, the local and wider contexts of action, and the values, preferences and actions of the local leaders, account should also be taken of the local union members" orientations, beliefs and willingness to participate in union activities and actions (Metochi, 2002), somewhat analogous to the current talk in the organizational leadership literature about "followership" (see, eg, Collison, 2005;Meindl et al, 2004;Shamir et al, 2007;Riggio et al, 2008;Ago, 2009). It is interesting to note, however, that , in a recent study of member activism and union organizing and renewal, found that "strategic and institutional" factors were central in explaining the source of bargaining power, rather than member activism, which was critical in some, but by no means all efforts at union renewal.…”
Section: Union Leadership: (Changing) Spaces and Conditionsmentioning
confidence: 99%